Vi Capsular Polysaccharide Produced by Recombinant Salmonella enterica Serovar Paratyphi A Confers Immunoprotection against Infection by Salmonella enterica Serovar Typhi - Xiong, Kun; Zhu, Chunyue; Chen, Zhijin; Zheng, Chunping; Tan, Yong; Rao, Xiancai; Cong, Yanguang (Frontiers in Cellular and Infection Microbiology, 2017)
Enteric fever is predominantly caused by Salmonella enterica serovar Typhi and Salmonella enterica serovar Paratyphi A, and accounts for an annual global incidence of 26.9 millions. In recent years, the rate of S. Paratyphi A infection has progressively increased. Currently licensed vaccines for typhoid fever, live Ty21a vaccine, Vi subunit vaccine and Vi-conjugate vaccine, confer inadequate cross immunoprotection against enteric fever caused by S. Paratyphi A. Therefore, development of bivalent vaccines against enteric fever is urgently required. The immunogenic Vi capsular polysaccharide is characteristically produced in S. Typhi, but it is absent in S. Paratyphi A. We propose that engineering synthesis of Vi in S. Paratyphi A live-attenuated vaccine may expand its protection range to cover S. Typhi. In this study, we cloned the viaB locus, which contains ten genes responsible for Vi biosynthesis, and integrated into the chromosome of S. Paratyphi A CMCC 50093. Two virulence loci, htrA and phoPQ, were subsequently deleted to achieve a Vi-producing attenuated vaccine candidate. Our data showed that, despite more than 200 passages, the viaB locus was stably maintained in the chromosome of S. Paratyphi A and produced the Vi polysaccharide. Nasal immunization of the vaccine candidate stimulated high levels of Vi-specific and S. Paratyphi A-specific antibodies in mice sera as well as total sIgA in intestinal contents, and showed significant protection against wild-type challenge of S. Paratyphi A or S. Typhi. Our study show that the Vi-producing attenuated S. Paratyphi A is a promising bivalent vaccine candidate for the prevention of enteric fever.